2021
DOI: 10.3390/pr9010081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Ni-Co/Al-Mg Catalyst Loading in the Continuous Aqueous Phase Reforming of the Bio-Oil Aqueous Fraction

Abstract: The effect of catalyst loading in the Aqueous Phase Reforming (APR) of bio-oil aqueous fraction has been studied with a Ni-Co/Al-Mg coprecipitated catalyst. Because of the high content of water in the bio-oil aqueous fraction, APR could be a useful process to convert this fraction into valuable products. Experiments of APR with continuous feeding of aqueous solution of acetol, butanol and acetic acid as the only compound, together with a simulated and a real aqueous fraction of bio-oil, were carried out. Liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Comparing the results obtained in the current work with those reported in literature, Lozano et al [35] observed CCgas values of 45-50 % and hydrogen content in the gas of 33.7 % using different catalyst load and similar operating conditions. Callison et al [55] reported lower hydrogen production values (0.4 mmol H 2 and 0.2 mmol CH 4 vs 5.75 mmol H 2 and 1.96 mmol CH 4 ), using similar reaction conditions but much higher initial hydroxyacetone concentration (10 vs 1% wt.…”
Section: Apr Of Individual Model Compoundssupporting
confidence: 87%
See 2 more Smart Citations
“…Comparing the results obtained in the current work with those reported in literature, Lozano et al [35] observed CCgas values of 45-50 % and hydrogen content in the gas of 33.7 % using different catalyst load and similar operating conditions. Callison et al [55] reported lower hydrogen production values (0.4 mmol H 2 and 0.2 mmol CH 4 vs 5.75 mmol H 2 and 1.96 mmol CH 4 ), using similar reaction conditions but much higher initial hydroxyacetone concentration (10 vs 1% wt.…”
Section: Apr Of Individual Model Compoundssupporting
confidence: 87%
“…Some studied have reported that catalyst deactivation in the APR of acetic acid and ethanol is not relevant [39]. However, Lozano et al [35], found low reactivity of acetic acid in APR using Ni-Co/Al-Mg catalysts, especially compared to ethanol, due to catalyst deactivation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation